Comparative analysis of the physicochemical properties and trace metal content of palm oil, from selected markets in Jos south and Jos north LGA, Plateau state, Nigeria: Comparative Analysis of the Physico-Chemical Properties and Trace Metal Content of Palm Oil - J. R, Gungshik; O. A, Onyemowo; L. A, Rabiat (International Journal of Advanced Chemistry, 2024)
The quality of palm oil samples collected from three different markets in Jos South and Jos North Local Government Area of Plateau State were analyzed and evaluated using standard analytical laboratory procedures. The relative ranges of the physicochemical values obtained were as follows; Moisture Content (MC): 0.56 - 1.89, Iodine value (IV); 51.88 - 55.57 g I2/100g, Peroxide Value (PV): 0.98 - 4.16 mEq02/kg, Saponification Values (SV): 198.46 - 201.54 mgKOH/g, Acid Value (AV): 9.93 - 57.65, and Refractive Index (RI), 1.4576 - 1.4580. The moisture content, iodin value, pH values and acid values were found to exceed the Standard Organization of Nigeria (SON) permissible limits of moisture content (0.29 mgKOH/g), iodine value (45 - 53 mg I2/100g), pH (5 - 7 mg/L), and acid value (0.7 max mg/L) for edible oils respectively while the refractive index, saponification values, peroxide values falls within the SON allowable limits of refractive index (1.4612-1.4707 mg/L), saponification value (195-205 mgKOH/g) and peroxide value (10 mEq02/kg) respectively . The amounts of trace metals (Cu, Zn, Fe, Pb and Cd) determined in the palm oil using the atomic absorption spectrophotometer ranged from Cu(0.34 - 0.52 mg/l), Zn(1.58 - 2.33 mg/l), Fe(19.18 - 26.74 mg/l), Pb(2.87 - 4.06 mg/l) and Cd(1.58 - 2.24 mg/l). However, the levels of Zn, Fe, Pb and Cd exceeded the WHO/FAO recommended values of (1.50, 1.00, 0.05 and 0.02 mg/L) respectively while only Cu concentration was below the WHO/FAO limits of 2.00 mg/L for trace metals in edible palm oil. Consequently, the results of this study shows that the palm oil consumed from these selected markets does not meet the standard quality specification for edible palm oils and hence can post significant health threat to consumers. Therefore, food regulatory agencies should strengthen their surveillance to promote food and health safety of the populace.